Intravascular lithotripsy in the treatment of peripheral artery disease - Michał Dobrzyński; Jakub Czarnota; Tomasz Skubel; Dorota Sokół; Małgorzata Drozd; Iga Dudek; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Peripheral artery disease (PAD) is an atherosclerotic process leading to narrowing of the major distal arteries in relation to the aortic arch. The progressive closure of the artery leads to its narrowing, reduced blood flow and the appearance of intermittent claudication - the most common symptom among patients. Standard methods of management include drug treatment and lifestyle modification. In severe cases, surgical treatment is used, including intravascular lithotripsy (IVL). The aim of the study is to analyze the available data on the treatment of peripheral arterial disease with IVL. The work uses the latest data published on the PubMed platform. The efficacy of lithotripsy in the treatment of PAD has been confirmed in numerous publications. The therapeutic effect was obtained both using the lithotripsy procedure alone as well as in combination with other methods modifying atherosclerotic plaque. IVL is a safe method, the number of observed complications was negligable. After the patient is properly qualified for the procedure, IVL may become the therapy of choice in the treatment of PAD.